Ferroelectricity in Rare-Earth Modified Hafnia Thin Films Deposited by Sequential Pulsed Laser Deposition. (12th September 2015) - Sharma, Yogesh; Barrionuevo, Danilo; Agarwal, Radhe; Pavunny, Shojan P.; Katiyar, Ram S.
Abstract : Room temperature ferroelectricity in pulsed laser deposited rare-earth doped hafnium oxide (HfO2 ) thin films is discussed. Maximum values of remnant polarizations (Pr ) ∼13.5 and 12 μC/cm 2 along with coercive fields (EC ) ∼334 and 384 kV/cm are observed in 6 mol. % of rare-earth (Sm or Gd) doped-HfO2 thin films (Sm:HfO2 and Gd:HfO2 ), respectively. Piezoresponse force microscopy measurements confirmed ferroelectric nature of films by showing phase hysteresis and butterfly amplitude loops. It is noticed that wake-up cycles improved the remnant polarization and found to be necessary for the forming of well saturated hysteresis loops. Our results showed potential toward realization of future highly scaled non-volatile ferroelectric memories.